Structural and functional synthesis of the radioelectronic means of a pulsed NQR - Samila, Andriy; Haliuk, Serhii; Krulikovskyi, Oleh (Stefan cel Mare University of Suceava, 2020)
The principles of structural and functional synthesis of the radioelectronic means of a pulsed NQR are presented. To simulate signal transformations in the radio frequency paths of the spectrometer, an imitation model of the direct pulsed NQR observation method was developed in the MATLAB Simulink software. The feature of the proposed measuring setup is the implementation of all algorithms for digital processing and signal synthesis in the basis of one FPGA Cyclone IV. The NQR spectrum is reconstructed from the spin induction signal using the fast Fourier transform method.
Keywords: nuclear imaging; chemical and biological sensors; computer simulation; fast Fourier transforms